Hawthorn (Crataegus pinnatifida Bunge) leave flavonoids attenuate atherosclerosis development in apoE knock-out mice. (23rd February 2017) - Dong, Pengzhi; Pan, Lanlan; Zhang, Xiting; Zhang, Wenwen; Wang, Xue; Jiang, Meixiu; Chen, Yuanli; Duan, Yajun; Wu, Honghua; Xu, Yantong; Zhang, Peng; Zhu, Yan
Abstract: Ethnopharmacological relevance: Hawthorn ( Crataegus pinnatifida Bunge) leave have been used to treat cardiovascular diseases in China and Europe. Hawthorn leave flavonoids (HLF) are the main part of extraction. Whether hawthorn leave flavonoids could attenuate the development of atherosclerosis and the possible mechanism remain unknown. Materials and methods: High-fat diet (HFD) mixed with HLF at concentrations of 5 mg/kg and 20 mg/kg were administered to apolipoprotein E (apoE) knock out mice. 16 weeks later, mouse serum was collected to determine the lipid profile while the mouse aorta dissected was prepared to measure the lesion area. Hepatic mRNA of genes involved in lipid metabolism were determined. Peritoneal macrophages were collected to study the impact of HLF on cholesterol efflux, formation of foam cell and the expression of ATP binding cassette transporter A1 (ABCA1). Besides, in vivo reverse cholesterol transport (RCT) was conducted. Results: HLF attenuated the development of atherosclerosis that the mean atherosclerotic lesion area in en face aortas was reduced by 23.1% (P<0.05). In mice fed with 20 mg/kg HLF, Total cholesterol (TC) level was decreased by 18.6% and very low density lipoprotein cholesterol plus low density lipoprotein cholesterol (VLDLc+LDLc) level were decreased by 23.1% whereas high density lipoprotein cholesterol (HDLc) and triglyceride (TG) levels were similar compared to that of the control group. Peroxisome proliferator activated receptor alpha (PPARα) mRNA was increased by 31.2% (P<0.05) and 60.9% (P<0.05) in mice fed with 5 mg/kg and 20 mg/kg HLF respectively. Sterol regulatory element binding protein-1c (SREBP-1c) was decreased by 59.3% in the group of 20 mg/kg. Carnitine palmitoyl transferase 1 (CPT-1) mRNA level of 20 mg/kg group was induced 66.7% (P<0.05). Superoxide dismutase 1 and 2 (SOD1 and SOD2) mRNA were induced 25.4% (P<0.05) and 71.4% (P<0.05) while induced by 36.3% (P<0.05) and 73.2% (P<0.05) in group of 20 mg/kg. Glutathione peroxidase 3 (Gpx3) mRNA in the group of 20 mg/kg was induced by 96.7% (P<0.05). Hepatic hydroxymethylglutaryl CoA reductase (HMG-CoAR) expression was as same level as the control group while LDL receptor (LDLR) mRNA and protein were induced by 84.2% (P<0.05) and 98.8% (P<0.05) in group of 20 mg/kg. HLF inhibit the formation of foam cell by 27.9% (P<0.05) in the dosage of 25 μg/ml, and 33.3% (P<0.05) in the dosage of 50 μg/ml. HLF increased the reverse cholesterol transport (RCT) in vivo . Discussion and conclusion: Hawthorn leave flavonoids can slow down the development of atherosclerosis in apoE knockout mice via induced expression of genes involved in antioxidant activities, inhibition of the foam cell formation and promotion of RCT in vivo, which implies the potential use in the prevention of atherosclerosis. Graphical abstract: